Te Ana o te Raiona: Māori Political Movements and the Māori Seats in Parliament, 1867 – 2008. - McDowell, Tiopira (The University of Auckland, 2013)
In 1867 the New Zealand Parliament passed legislation to introduce four seats in the House of Representatives for the Māori people, the indigenous tribes of Aotearoa-New Zealand. This thesis investigates the history of how Māori Members of Parliament and Māori political movements have engaged with the Māori seats from 1867 to 2008. It asks a series of questions on the nature of Māori political engagement with the Māori seats: Why were the Māori seats established and what role did Māori communities play in their establishment? Why did Māori choose to engage with parliament and how did they regard the Māori seats? What types of leaders did Māori political movements send to represent them, according to what criteria were those leaders selected, and how did Māori attitudes towards leadership change over time? What did Māori hope to achieve by sending their leaders to parliament, and what ambitions did those leaders carry with them? What have Māori parliamentarians in the Māori seats achieved and what factors have helped or hindered their efforts? How effective have Māori MPs been in representing their constituents in Parliament and by what criteria should we judge their effectiveness? And how has Māori political engagement with the Māori seats changed over time? This thesis also looks to the cultural and social implications of political engagement, asking what impact Māori culture, customs, language and social organisation had on Māori political engagement, and in turn what impact did political engagement with the Māori seats have on Māori culture and society? To answer these questions this thesis discusses the establishment of the Māori seats and the Māori political movements that have engaged with these seats, covering the formation of the seats 1835-1867, the careers of Māori MPs whose efforts and achievements are well established in the existing historical literature 1887-1943, the era of Ngā mātāmua the first wave of Māori MPs 1868-1938, the Rātana-Labour era, 1932-1960, the political career of Matiu Rata 1963-1991, and the formation of the Māori Party 1996-2008. This thesis employs a mix of primary documents, oral interviews and secondary sources to pull together a picture of Māori political engagement with the Māori seats over the past 145 years. It argues that historians have underestimated the role of the Māori MPs and the agency of Māori communities in determining the direction of political engagement. The Māori MPs have been dealt with in a homogenous fashion and written off as ineffective and ill prepared for the rigours of parliament. A closer reading demonstrates that the Māori MPs have made a considerable contribution to New Zealand society in pursuing the ambitions of their constituents, and that the Māori seats play a significant role in the social, cultural and political landscape of the nation.
Keywords: māori electorates; māori seats; political movements; ratana; te pāti māori

E-whanaungatanga : the role of social media in Māori political engagement - Waitoa, Joanne Helen (Massey University, 2013)
Social media are used increasingly worldwide to connect people and points of view. This thesis explores the role social media can play in enhancing Maori development via political engagement. It investigates the efficacy of using social media to increase Maori political awareness and participation using the Mana Party Facebook pages as a case study. It also examines the opportunities and implications of social media for indigenous development in general. Themes in the literature on social media and indigenous development include: identity politics; language revitalisation and cultural preservation; activism; knowledge management; networking and collaboration; and business and marketing. This qualitative study was informed by Kaupapa Maori and empowerment theories. It involves interviews with the Mana Party president, Mana Party Facebook page moderators, and users of the Mana Party Facebook pages. The interviews explored the objectives and outcomes of using social media to raise political awareness of Maori, finding that Mana Party objectives were met to varying degrees. It also found that social media has both positive and negative implications for indigenous development. Social media aligns with tikanga Maori through Tino Rangatiratanga and whanaungatanga. However, it can conflict with tikanga Maori due to lack of respect, cultural misappropriation, sharing sacred information, subversion of traditional hierarchy and absence of a ‘seen face’. There are thus tensions in the use of social media for political engagement among indigenous peoples. Finally, the thesis offers a framework of how to use social media with indigenous groups that emphasises the positive and mitigates the negative aspects of the platform.
Keywords: kāwanatanga; mana party; political participation; political parties